2022
DOI: 10.1155/2022/8950130
|View full text |Cite
|
Sign up to set email alerts
|

circ-Katnal1 Enhances Inflammatory Pyroptosis in Sepsis-Induced Liver Injury through the miR-31-5p/GSDMD Axis

Abstract: Background. Sepsis is a systemic inflammatory response that can elicit organ dysfunction as well as circulatory diseases in serious cases. When inflammatory responses are especially dysregulated, severe complications can arise, including sepsis-induced liver injury. Various microRNAs along with circular (circ) RNAs are involved in inflammatory responses; nevertheless, their functions in regulating sepsis-induced liver injury remain unknown. The cecal ligation and puncture (CLP) procedure can induce liver injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…However, Cai et al showed different results that miR-31-5p can activate MyD88-NF-κB -mediated microglial inflammation in rat subarachnoid hemorrhage model[ 48 ]. Other articles showed that the miR-31-5p/GSDMD Axis can regulate pyroptosis and miR-31-5p overexpressing can alleviate the level of TNF‐α, IL‐6 and IL‐1β in sepsis-induced pyroptosis [ 49 ]. NF-κB–responsive miR-31-5p led by TNF- α decrease eNOS expression in preeclampsia [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, Cai et al showed different results that miR-31-5p can activate MyD88-NF-κB -mediated microglial inflammation in rat subarachnoid hemorrhage model[ 48 ]. Other articles showed that the miR-31-5p/GSDMD Axis can regulate pyroptosis and miR-31-5p overexpressing can alleviate the level of TNF‐α, IL‐6 and IL‐1β in sepsis-induced pyroptosis [ 49 ]. NF-κB–responsive miR-31-5p led by TNF- α decrease eNOS expression in preeclampsia [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…MiR‐31‐5p is a highly conserved noncoding RNA involved in a variety of diseases, including sepsis 24 and colorectal cancer 25 . And it exhibits different regulatory effects in heart diseases.…”
Section: Discussionmentioning
confidence: 99%
“…CircHIPK3 promotes neuroinflammation through regulation of the miR-124–3p/STAT3/NLRP3 signaling pathway in Parkinson's disease ( Zhang et al., 2023 ). circ-Katnal1 enhances inflammatory pyroptosis in sepsis induced liver injury through the miR-31–5p/GSDMD axis ( Kang et al., 2022 ). Therefore, in this study, we focused our research on the regulation mechanism of pyroptosis on circRNAs.…”
Section: Discussionmentioning
confidence: 99%